Facial Exercise as an Effort to Improve Quality of Life in Elderly People With Xerostomia at Posyandu, Gedawang Village Banyumanik, Semarang - Wahyu Jati Dyah Utami; Sulur Joyo Sukendro; Prasko Prasko; Siti Mulidah (Jurnal Kesehatan Gigi, 2023)
ABSTRACT Background: The function of the organs of the elderly as they get older will decrease (organ degeneration), both due to natural factors and due to disease. An estimated 30% of seniors aged 65 years and older have decreased saliva production. Decreased saliva production causes complaints of dry mouth which is often known as xerostomia. This situation is caused by atrophy of the salivary glands (saliva) which will reduce salivary production and change its composition. The decreased salivary secretion will cause discomfort in the oral cavity, pain, and increased rates of dental caries and oral infections. Facial gymnastics is the act of giving massage to the facial area from top to bottom around the cheeks, mouth, and chin, this activity can stimulate the function of the oral cavity.Research objective: to analyze the effectiveness of facial exercises on the quality of life of elderly people with xerostomia.Research Methods: Quasi-experimental with pre-test and post-test design, a sample of 30 elderly people with xerostomia. Facial exercise treatment was carried out for 30 days, measurements were carried out using the Xerostomia Related Quality of Life Scale (XeQoLS). Questionnaires were given before and after treatment.Results: The results showed that after doing facial exercises there was an increase in salivary secretion from an average of 0.6 ml/per minute to 1.1 ml/per minute, and the results of the paired t-test p-value = 0.000. The majority of respondents had a low quality of life of 53% and after doing facial exercises the majority of respondents had a high quality of life of 57%, with the results of the paired t-test p-value = 0.000. This can happen because the implementation of facial exercises gets mechanical stimulation. The stimulation given can increase the flow of salivary secretion which directly affects the increase in saliva volume. The normal salivary secretion will cause a sense of comfort in the oral cavity, thereby increasing the quality of life of the elderly.